Intergenerational mobility in Ottoman Istanbul: Evidence from court records - Metin Murat Coşgel; José-Antonio Espín-Sánchez; Emre Özer (Yale University, Economic Growth Center, 2025)
We use data from the Istanbul court registers spanning from the 16th-19th centuries to establish, for the first time, long-term trends in intergenerational mobility in a major premodern city. The dataset contains information on over 270,000 individuals who appeared in court in various roles, including litigants, witnesses, and representatives. Crucially, it records the honorific titles (if any) of individuals and their fathers, which we use as measures for socioeconomic status. Our goal is to trace long-term changes in Istanbul's social structure, analyze the relationship between fathers' and sons' titles to assess shifts in intergenerational mobility, and determine whether these shifts reflect primarily horizontal movements within social strata or also include greater mobility across class boundaries. We find that the share of titled individuals followed a non-monotonic but ultimately upward trajectory between the sixteenth and nineteenth centuries. During the same period, the intergenerational transmission of titles declined, indicating increased mobility. However, this mobility was largely confined within the elite strata, suggesting a consolidation of power and status among the upper classes rather than a broad opening of the social hierarchy.
Keywords: J62; N3; 330; intergenerational mobility; Ottoman Empire; Istanbul; socio-economic status; honorific title; religious/judicial and military/administrative elite